Little Evidence of Zika Virus Infection in Wild Long-Tailed Macaques, Peninsular Malaysia - Chong Long Chua (Emerging Infectious Diseases, 2019)
We tested a sample of 234 wild long-tailed macaques (Macaca fascicularis) trapped in Peninsular Malaysia in 2009, 2010, and 2016 for Zika virus RNA and antibodies. None were positive for RNA, and only 1.3% were seropositive for neutralizing antibodies. Long-tailed macaques are unlikely to be reservoirs for Zika virus in Malaysia.